2017
DOI: 10.1590/2175-3539201702111080
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do treino em habilidades de consciência fonológica na escrita de pré-escolares

Abstract: Resumo Pesquisas recentes demonstram que aprender a ler e escrever em uma língua alfabética exige a compreensão da relação entre fonemas e grafemas, o que requer habilidades de segmentação da fala, isto é, consciência fonológica, sendo que tais habilidades têm se mostrado altamente correlacionadas à aprendizagem da língua escrita. Nesta pesquisa tivemos como objetivo avaliar os efeitos de um programa de intervenção em consciência fonológica sobre o desempenho em tarefas de escrita em 15 pré-escolares, os quais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 13 publications
(15 reference statements)
1
17
0
13
Order By: Relevance
“…Yet, as for the learning of speling, the greater opacity of the BP orthographic system requires the participation of phonemic awareness over a longer period, and the phonic method group was capable of developing the coding processes in a more significant way, probably due to having developed better phonological representations, and to having been exposed to the explicit teaching of orthographic-phonological correspondences. Therefore, the teaching method does seem to influence the process of learning to write in BP, with better results attributed to the phonics teaching method, which gives support to the mentioned Brazilian studies (Santos & Maluf, 2010;Santos & Barrera, 2017;Capovilla & Capovilla, 2000).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Yet, as for the learning of speling, the greater opacity of the BP orthographic system requires the participation of phonemic awareness over a longer period, and the phonic method group was capable of developing the coding processes in a more significant way, probably due to having developed better phonological representations, and to having been exposed to the explicit teaching of orthographic-phonological correspondences. Therefore, the teaching method does seem to influence the process of learning to write in BP, with better results attributed to the phonics teaching method, which gives support to the mentioned Brazilian studies (Santos & Maluf, 2010;Santos & Barrera, 2017;Capovilla & Capovilla, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…The studies in PB, especially those of phonological awareness training, have demonstrated the importance of this ability both to facilitate alphabetic learning (Capovilla & Capovolla, 2000;Santos & Maluf, 2010;Santos & Barrera, 2017) and to overcome learning difficulties in reading and writing (Justino & Barrera, 2012;Fukuda & Capellini, 2012). Some of these studies have emphasized the importance of the phonic approach, that is, the association of activities of phonemic awareness with the explicit teaching of the grapheme-phoneme correspondences and vice-versa.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results of studies that taught phonological awareness skills (Bandini, 2003;Bernadino Jr. et al, 2006;Capovilla et al, 2004;Freitas, 2008) and studies conducted on Child Education (Camilo & Mota, 2013;Moreschi & Barrera, 2017;Pestun, Omote, Barreto, & Matsuo, 2010;Santos & Maluf, 2010;Santos & Barrera, 2017), which demonstrated the importance of stimulating phonological awareness for the development of reading and writing skills, we suggest that future studies develop teaching programs for phonological awareness conducive to the development of educational strategies that facilitate and lead to the acquisition of reading and writing skills.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the development of phonological awareness (awareness of the sounds that constitute speech) is related to successful learning of reading and writing (Barrera & Maluf, 2003;Capovilla, Gütschow, &Capovilla, 2004;Justino & Barrera, 2012;Moreschi & Barrera, 2017;Nunes, Frota, & Mousinho 2009;Puliezi & Maluf, 2012;Santos & Maluf, 2010;Santos & Barrera, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que crianças menores já são capazes de efetuar a manipulação em um nível silábico (palavras e sílabas), que são aprendidas anteriormente às habilidades intrassilábicas (aliteração e rima) e, estas ultimas, anteriormente ao nível fonêmico (fonemas) (37,38) . (37,38) .…”
Section: Habilidades Metalinguísticasunclassified